Life Cycle Assessment as a tool to promote sustainable Thermowood boards: a Portuguese case study - Ferreira, J. (2016)
The present work aims to develop the Life Cycle Assessment study of thermo-modified Atlanticwood® pine boards based on real data provided by Santos & Santos Madeiras company. Atlanticwood® pine boards are used mainly for exterior decking and cladding facades of buildings. The LCA study is elaborated based on ISO 14040/44 standard and Product Category Rules for preparing an environmental product declaration for Construction Products and Construction Services. The inventory analysis and, subsequently, the impact analysis have been performed using the LCA software SimaPro8.0.4. The method chosen for impact assessment was EPD (2013) V1.01. The results show that more than ¾ of ‘Acidification’, ‘Eutrophication’, ‘Global warming’ and ‘Abiotic depletion’ caused by 1 m3 of Atlanticwood® pine boards production is due to energy consumption (electricity + gas + biomass). This was to be expected since the treatment is based on heat production and no chemicals are added during the heat treatment process.